Analysis of the Relationship between Knowledge About Schizophrenia and Family Support on Medication Adherence Among Those Undergoing Repeated Treatment at Dr. Soeharto Heerdjan Mental Hospital - Aisah Mamang; Syamsul Anwar; Nurhayati Nurhayati (UIMA Press, 2024)
Background: Schizophrenia is a severe mental disorder characterized by difficulties in thought processes. One of the factors influencing repeated hospitalizations in patients with schizophrenia is the knowledge about schizophrenia and family support, which can lead to medication non-adherence. Methods: This study employs a cross-sectional approach with 129 participants who have a family member experiencing repeated hospitalizations or long-term patients diagnosed with schizophrenia at dr. Soeharto Heerdjan Psychiatric Hospital. The sampling data collection technique uses probability. Data were collecte using questionnaire with a reliability value for knowledge about schizophrenia (KASQ) of 0.945, informational support 0.935, assessment/award support 0.915, emotional 0.907, and medication adherence (MARS) 0.960. Bivariate data analysis using logistic regression and multivariate data using the multiple logistic regression test. Results: The research result showed that the majority of respondents had insufficient knowledge 47.3 % with a p-value of 0.000 that there was a significant relationship between family knowledge about schizophrenia and adherence to taking medication. Informational support is 66.7% lacking with a p-value 0.000 a significant relationship between infomational support and medication adherence. Support for assessment/reward is less that 78.3% with a p-value 0.000 that there is significant relationship between support for assessment/reward and adherence to taking medication. Instrumental support wasl 77.5% with a p-value 0.000 that there was a significant relationship between instrumental support and compliance with taking medication. Emotional support was less at 77.5% with a p-value 0.000 that there was significat reletionship between emotional support and compliance with taking medication. The dominant factor among families of patients diagnosed with schizophrenia experiencing repeated hospitalizations at dr. Soeharto Heerdjan Psychiatric Hospital was the variable of family informational support with an odds ratio of 32.003. This indicates that families with informational support are 32 times more likely to have repeated hospitalizations compared to families without informational support, after controlling for variables of knowledge about schizophrenia, family instrumental support, and family appraisal/esteem support. Conclusion: There is a relationship between knowledge about schizophrenia, informational support, appraisal/esteem support, instrumental support, and emotional support with medication adherence.